64. Differences in intracortical inhibition of tongue motor representations between persistent adult developmental stutterers and normal speakers. Issue 4 (April 2016) - Busan, P.; Del Ben, G.; Monti, F.; Battaglini, P.P.
Abstract : The causes of developmental stuttering are not known, but increasing evidence shows differences in the motor system of persistent adult developmental stutterers (PADS) in comparison to normal speakers (NS). Right handed males PADS and matched NS (considering age, sex, handedness, smoking habits and musical expertise) were evaluated by using transcranial magnetic stimulation on their tongue primary motor cortex. We assessed resting and active motor thresholds, silent period threshold (SPT), and silent period duration (SPD, stimulating at 130% of SPT) in both hemispheres. Preliminary results suggest the presence of higher SPT for the PADS group with respect to NS. Moreover, SPD were increased in the left hemisphere of PADS with respect to NS. This result suggests a particular intracortical balance in the tongue motor cortex of PADS compared to NS. More specifically, while the higher SPT in PADS could suggest a lower intracortical inhibition, the longer SPD in the left hemisphere of PADS points up to a greater inhibition in these brain regions, thus compensated by the presence of lower inhibition in the right hemisphere of the same group. This data, in line with previous evidence in stuttering research, could be useful for rehabilitative purposes.